2004
DOI: 10.1074/jbc.m404488200
|View full text |Cite
|
Sign up to set email alerts
|

The Proline-rich Homeodomain Protein Recruits Members of the Groucho/Transducin-like Enhancer of Split Protein Family to Co-repress Transcription in Hematopoietic Cells

Abstract: The proline-rich homeodomain protein (PRH/Hex) is important in the control of cell proliferation and differentiation and in the regulation of multiple processes in embryonic development. We have shown previously that PRH contains two domains that can independently bring about transcriptional repression. The PRH homeodomain represses transcription by binding to TATA box sequences, whereas the proline-rich N-terminal domain of PRH can repress transcription when attached to a heterologous DNA-binding domain. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(119 citation statements)
references
References 71 publications
5
114
0
Order By: Relevance
“…PRH N187A contains a mutation in the PRH homeodomain and is unable to bind DNA (4,27). PRH F32E contains a mutation that blocks the binding of PRH to co-repressor proteins belonging to the TLE family (3,27). Both of these mutated proteins show a significantly reduced ability to inhibit cell migration compared to wild type PRH (Fig.2B) although all three proteins are expressed at roughly equivalent levels (Fig.2C).…”
Section: Prh Over-expression Inhibits Prostate Cancer Cell Migration mentioning
confidence: 99%
See 2 more Smart Citations
“…PRH N187A contains a mutation in the PRH homeodomain and is unable to bind DNA (4,27). PRH F32E contains a mutation that blocks the binding of PRH to co-repressor proteins belonging to the TLE family (3,27). Both of these mutated proteins show a significantly reduced ability to inhibit cell migration compared to wild type PRH (Fig.2B) although all three proteins are expressed at roughly equivalent levels (Fig.2C).…”
Section: Prh Over-expression Inhibits Prostate Cancer Cell Migration mentioning
confidence: 99%
“…A rabbit polyclonal antibody was used to detect Endoglin (Abcam). PRH antibodies have been described previously (3,42). Lamin A/C and Tubulin antibodies were from Santa-Cruz.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…107,108 For HHEX and TLX1, it has been shown that the interaction with TLE proteins is important in regulating downstream targets in hematopoietic lineages and in T-ALL. 52,109 Binding of TLE can result in repression of transcription of NKL targets, but it can also act as a competitive substrate for TLE proteins relieving other factors from TLE-mediated repression and activation of transcription. 110 For example, TLX1 expression enhances NOTCH1 signaling in a T-ALL cell line, partly by sequestering TLE from the Hairy/Enhancer of split 1 -TLE-mediated transcriptional repression complex.…”
Section: Nkls Modes Of Actionmentioning
confidence: 99%
“…TLE1 is one of four TLE (Transducin-Like Enhancer of split) genes that encode human transcriptional repressors homologous to the Drosophila corepressor groucho (30); differential overexpression of TLE2, 3 and 4 has also been demonstrated in synovial sarcoma (1,3,25). TLE proteins are temporally expressed in embryogenesis where they are involved in developmental processes including neurogenesis, body patterning and hematopoesis (6,30,31,34). The repressive effect of Groucho and TLE1 is dependent on phosphorylation status and involves histone deacetylase (HDAC) activity (4,7,16,26,35).…”
Section: Introductionmentioning
confidence: 99%